Treatment of rheumatoid arthritis by the induction of regulatory cells: BiP is a promising candidate - Panayi, Gabriel (Henry Stewart Talks, 2010)
BiP is a molecular chaperone found within the endoplasmic reticulum, It protects cells from damage and death by stress, It can also appear outside the cell when it engages an as yet undefined cell membrane receptor, which alters monocyte differentiation and function, BiP can prevent and treat collagen induced arthritis by a single intravenous or a single subcutaneous injection of BiP, This therapeutic effect appears to be linked at least in part to the production of interleukin 4, Lymph node and spleen cells from mice injected with BiP can prevent and treat ongoing arthritis when transferred intravenously into recipient mice without the necessity of additional BiP having to be given, BiP given intravenously to severe combined immunodeficiency mice bearing subcutaneous, vascularised implants of rheumatoid arthritis synovial membrane will ablate inflammatory cells and cytokines from the implants